Role of osteopontin, a multifunctional protein, in allergy and asthma - Konno, S.; Kurokawa, M.; Uede, T.; Nishimura, M.; Huang, S.-K. (Clinical and experimental allergy, 2011)
Summary Osteopontin (OPN) is an extracellular matrix protein and immune modulator with a wide range of functions. OPN is recognized as a key cytokine in Th1 immune responses, yet its potential involvement in allergic/asthmatic responses has been investigated only recently. Current data from molecular and cellular studies and studies of OPN‐deficient mice provide evidence that OPN plays multiple roles in the regulation of allergic responses, including regulation of IgE response, inflammatory cell migration, and the development of airway fibrosis and angiogenesis. These results suggest that OPN is a pleiotropic cytokine that functions both systemically and locally in tissue mucosa. Notably, OPN is able to exert its effects through different functional domains, and the secreted and intracellular forms of OPN may have distinct functions. Future research to elucidate all aspects of OPN function is needed to ultimately establish its role in the regulation of immune responses and various disease processes, including those critically involved in the development of allergies and asthma. Cite this as: S. Konno, M. Kurokawa, T. Uede, M. Nishimura and S.‐K. Huang, Clinical & Experimental Allergy, 2011 (41) 1360–1366.